Metformin in the treatment of colorectal cancer and neuroendocrine tumours - Daniłowska, Karolina; Picheta, Natalia; Krupska, Barbara I.; Rudzińska, Anna; Burdan, Oliwia; Szklener, Katarzyna (Contemporary Oncology/Współczesna Onkologia, 2024)
Colorectal cancer is being detected in increasingly younger age groups, and its incidence has been on the rise in recent years. Neuroendocrine tumors have also shown an increase in occurrence despite their rarity. Neuroendocrine tumors most commonly occur in the gastrointestinal tract and lungs. Therefore, new, better, and more effective treatment methods are being sought. Metformin, a drug commonly used in the treatment of type 2 diabetes, has demonstrated its ability to reduce the incidence and increase the efficacy of chemotherapy in colorectal cancer and neuroendocrine tumors. The biguanide works by inhibiting the mammalian target of rapamycin pathway, activating 5’AMP activated protein kinase, and reducing insulin-like growth factor 1. In studies conducted on human cells and xenografts, the drug has shown its positive effects in combating these tumors by reducing proliferation, slowing the growth of cancer cells, and inhibiting metastasis. The main goal of this review is to comprehensively summarize the current state of knowledge regarding metformin in the treatment of colorectal cancer and neuroendocrine tumors.